2005
DOI: 10.1074/jbc.m504852200
|View full text |Cite
|
Sign up to set email alerts
|

The p53-induced Gene-6 (Proline Oxidase) Mediates Apoptosis through a Calcineurin-dependent Pathway

Abstract: Proline oxidase is a p53-induced redox gene that can generate reactive oxygen species (ROS) and mediate apoptosis in tumor cells. We report that proline oxidase is a downstream effector in p53-mediated activation of the calcium/calmodulin-dependent phosphatase calcineurin in lung, renal, colon, and ovarian carcinoma cells. The activation of calcineurin by p53 and proline oxidase was detected by activation of the nuclear factor of activated T cells (NFAT), an established indicator of activated calcineurin. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
100
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(103 citation statements)
references
References 65 publications
(68 reference statements)
0
100
0
Order By: Relevance
“…Proline metabolism has generally been considered to generate a more oxidative environment via mitochondrial PRODH activity [3][4][5][6]47,63,64]. Here, we have shown that PRODH generates superoxide directly during turnover with proline.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Proline metabolism has generally been considered to generate a more oxidative environment via mitochondrial PRODH activity [3][4][5][6]47,63,64]. Here, we have shown that PRODH generates superoxide directly during turnover with proline.…”
Section: Discussionmentioning
confidence: 59%
“…Of the proline metabolic genes used in this study, most is known about the regulation of PRODH gene expression in cellular apoptosis. Different studies have established that PRODH is activated by p53 and the peroxisome proliferator-activated receptor gamma (PPARγ) regulator with increased PRODH expression leading to oxidative stress [3][4][5][6][7][8]. Hepatocyte nuclear factors HNF4α and HNF1α have also been found to regulate proline degradation [61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that metabolism genes, for example proline oxidase [28,29] and cytosolic phospholipase A2 [30,31], were differentially expressed in tumor cells and might have a role in carcinogenesis. Many metabolism genes with abnormal expression in ccRCC tissues, including ASS, were identified by our investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The oligo-capping method was performed as described previously [29]. Briefly, the phosphate of the 5¢-ends of truncated mRNAs was hydrolyzed by bacterial alkaline phosphatase (Takara).…”
Section: Construction Of Full-length Cdna Librarymentioning
confidence: 99%